Direct and residual effects of chicken manure on soil air dry bulk density and moisture content of a desert plain soil and wheat (Triticum aestivum L.) yield, Northern State, Sudan - Ahmed, Imran; Ahmed, Mahamuod; Hamad, Muawia (Gezira Journal of Agricultural Science; Vol 16 No 1 (2018), 2018)
This study was conducted for three consecutive seasons 2014/15 (direct effect), 2015/16 (direct and residual effects)  and 2016/17 (residual effect) on a desert soil with the aim to investigate direct and residual effects of chicken manure on air dry bulk density and moisture content of a desert plain soil as well as grain yield of wheat in the Northern State, Sudan. The chicken manure was used at four levels (0, 4, 8, and 12 ton ha -1 ). The treatments were arranged in a randomized complete block design with three replicates. Land preparation was done manually for the residual effects of chicken manure so as not to mix the treatments which were fixed in the same plots of the first application of the manure. The results showed that the direct and residual effects of  chicken manure were effective in improving soil physical properties. The soil air dry bulk density was very highly significantly (P≤0.001) reduced on the average across the two seasons and varied from 1.67 g cm -3 for  the control treatment to 1.39 g cm -3 for the chicken manure treatments in  the direct effect and from 1.60 g cm -3 to 1.33 g cm -3 for the residual effect. The total pore space (porosity) increased very highly significantly(P≤0.001)  on average across the seasons and varied from 36 % for the control treatment  to 47.1% for the chicken manure treatments for the direct effect and from 38% to 49.1% for the residual effect  in response to the application of  the organic manure. The direct and residual effects of chicken manure very highly significantly (P≤0.001) increased the soil moisture percentage on the average across both seasons and varied from 9.4% in the control to 16.9% for the direct effect and from 10.5% to 19.6% for the residual effect in the top soil (30 cm soil depth).The results indicated that the direct and residual effects of chicken manure gave very highly significant (P≤0.001) increases in the grain yield of wheat on the average across the seasons and varied from 0.72 in the control treatment to 3.75 ton ha -1 in the direct effect and 1.87  to 5.54 ton ha -1 for the residual effect in this desert plain soil. It is recommended that 4 ton ha -1 of chicken manure can be applied to reclaim these desert plain soils and increase wheat yield in the Northern Sudan تضمنت الدراسة تجربة نفذت خلال ثلاثة  مواسم متتالية 2014/15 (الأثر المباشر) و2015/16 (الأثر المباشر والباقي) و2016/17 (الأثر الباقي)  في تربة صحراوية بهدف معرفة الأثر المباشر والباقي لسماد زرق الدواجن بأربعة مستويات (0 و 4 و 8 و 12 طن/ هكتار) على الكثافة الظاهرية ومحتوى الماء لتربة السهل الصحراوي وإنتاجية القمح بالولاية الشمالية بالسودان. نفذت التجربة على نظام القطاعات العشوائية الكاملة لثلاث مكررات. تم تحضير ارض التجربة يدويا حتى تحتفظ وحدات التجربة بنفس معاملات السنة الأولى وذلك لمعرفة الأثر الباقي لسماد زرق الدواجن. أوضحت النتائج أن الأثر المباشر و الباقي لسماد زرق الدواجن فعال في تحسين الخواص الطبيعية للتربة. وجد تناقص معنوي عال جدا (P≤0.001) في قيمة الكثافة الظاهرية للتربة في المتوسط للموسمين من 1.67  في الشاهد إلى 1.39 جرام/ سم 3 في معاملات سماد زرق الدواجن بالنسبة للأثر المباشر لسماد زرق الدواجن حيث تناقصت الكثافة الظاهرية من 1.60 إلى 1.33 جرام/ سم 3 بالنسبة للأثر الباقي لسماد زرق الدواجن. بينما حدثت زيادة معنوية عاليه جدا (P≤0.001) في مسامية التربة  في المتوسط للموسمين من 36 % في الشاهد إلى 47.1 % للأثر المباشر لمعاملات سماد زرق الدواجن أما بالنسبة للأثر الباقي كانت الزيادة في المتوسط للموسمين من 38% في الشاهد إلى 49% لمعاملات سماد زرق الدواجن. و أيضا أن سماد زرق الدواجن و أثره الباقي له اثر معنوي عالي جدا في زيادة  النسبة المئوية لماء التربة حيث كانت الزيادة في المتوسط للموسمين من 9.4 % في الشاهد إلى 16.9 % للأثر المباشر لسماد زرق الدواجن ومن 10.5 % في الشاهد إلى 19.6 % للأثر الباقي  لسماد زرق الدواجن في عمق 30سم من سطح التربة. أظهرت نتائج البحث أن الأثر المباشر والباقي لسماد زرق الدواجن له أثر معنوي عال جدا (P≤0.001) في زيادة إنتاجية محصول القمح في المتوسط للموسمين من 0.72 طن/هكتار في الشاهد إلى 3.75 طن/هكتار للأثر المباشر لمعاملات سماد زرق الدواجن ومن 1.87 طن/هكتار في الشاهد إلى 5.54 طن/هكتار للأثر الباقي لسماد زرق الدواجن  بتربة السهل الصحراوي. توصى الدراسة بان إضافة 4 طن/هكتار من سماد زرق الدواجن هي الأفضل لاستصلاح ترب السهل الصحراوي وزيادة إنتاجية القمح بشمال السودان.